Not just political parties: Robert Michels as a critic of mainstream economics - Susca, Emanuela (Frontiers in Sociology, 2023)
Best known for his contribution to elite theory through the formulation of the principle of oligarchy, Robert Michels pursued a critique of economic reductionism for decades. In this paper, I examine some significant passages from Michels’ writings to clarify the significance of his criticism of the dominant economics of his time. This provides an overview of an author partly conditioned by his adherence to Italian fascism but still able to distance himself progressively from productivist ideology while anticipating current lines of research focusing on the relationship between the market and society, such as civil economy. Moreover, by investigating how goods may provide happiness, Michels expressed a sophisticated and contemporary view of consumption, already bringing into focus the logic of distinction that Pierre Bourdieu examined in the second half of the twentieth century. By also attempting to do all this in an interdisciplinary way, Michels represents a scholar whom the social sciences and sociology should rediscover in the face of the challenges of the twenty-first century.